Time‐course of sodium transport along the nephron in nephrotic syndrome: The role of potassium. Issue 2 (29th December 2019) - Dizin, Eva; Olivier, Valérie; Maire, Charline; Komarynets, Olga; Sassi, Ali; Roth, Isabelle; Loffing, Johannes; de Seigneux, Sophie; Maillard, Marc; Rutkowski, Joseph M.; Edwards, Aurélie; Feraille, Eric
Abstract: The mechanism of sodium retention and its location in kidney tubules may vary with time in nephrotic syndrome (NS). We studied the mechanisms of sodium retention in transgenic POD‐ATTAC mice, which display an inducible podocyte‐specific apoptosis. At day 2 after the induction of NS, the increased abundance of NHE3 and phosphorylated NCC in nephrotic mice compared with controls suggest that early sodium retention occurs mainly in the proximal and distal tubules. At day 3, the abundance of NHE3 normalized, phosphorylated NCC levels decreased, and cleavage and apical localization of γ‐ENaC increased in nephrotic mice. These findings indicate that sodium retention shifted from the proximal and distal tubules to the collecting system. Increased cleavage and apical localization of γ‐ENaC persisted at day 5 in nephrotic mice when hypovolemia resolved and steady‐state was reached. Sodium retention and γ‐ENaC cleavage were independent of the increased plasma levels of aldosterone. Nephrotic mice displayed decreased glomerular filtration rate and urinary potassium excretion associated with hyperkaliemia at day 3. Feeding nephrotic mice with a low potassium diet prevented hyperkaliemia, γ‐ENaC cleavage, and led to persistent increased phosphorylation of NCC. These results suggest that potassium homeostasis is a major determinant of the tubular site of sodium retention in nephrotic mice.